Intentionality and Conventional Meaning (Socio-Historical Approach) - Davidko, Natalya (Verbum, 2011)
Linguistic studies of collective consciousness are practically nonexistent though insightful ideas are found in works of many linguists (Chomsky 1985, Fowler 1996). The central tenet of this paper is that archetypes (mental representations of concepts in collective consciousness) are built around socially significant experiences of people and comprise meanings which incarnate collective sentiments and ideologies. The number and composition of such meanings can change and vary due to an interplay of environmental factors – social, political, economic, cultural, etc. – and can be drawn from discourses which perform an ideational function concerned with the representation of world views in a language. Two propositions are preconditional for the present research: first, the acknowledgement of the force of authorial intent (intentionality) in discourse and, second, the assumption that over a long history, language has learnt to suit the needs of the society it functions in (mainly the needs of dominant social groups) by legitimatizing some meanings (conventional meanings) and rejecting others. The concept chosen for the analysis is monetary DEBT. Debt plays an important role both in the economic life of a country and in private lives of individuals. The attitude to debt has been changing throughout the history, and we hypothesize that economic discourses have had a major impact on collective perception of the concept in question.
Keywords: collective consciousness; archetype; archetypal meaning; discourse; intentionality; ideational meaning; conventional meaning.